Composing the Soundscape: Ecological Listening in the Music of John Luther Adams. - Hanslowe, Thomas. (2017)
Abstract: This thesis explores the connections between John Luther Adams's music and his environmentalist politics. Drawing on recent writings in ecomusicology, as well as the work of John Cage and R. Murray Schafer, this thesis takes three of Adams's pieces as case studies, In the White Silence (1998), a concert piece, The Place Where You Go to Listen (2004-6), a sound and light installation, and Inuksuit (2009), an outdoor piece. These pieces provide a lens to examine how Adams connects his music to "ecological listening." I argue that Adams's music creates political meaning by suggesting listening to environmental sounds can connect us deeply with our place on earth and breaks down what he views as artificial barriers between humanity and nature. This thesis aims to deepen our understanding of both Adams's work and the political role of music in a time of environmental crisis.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Music.; Advisor: Joseph Auner.; Committee: Frank Lehman, and Alessandra Campana.; Keywords: Music, Ecology, and American studies.